1998
DOI: 10.1590/s0101-81751998000300003
|View full text |Cite
|
Sign up to set email alerts
|

Nest structure and communal nesting in Euglossa (Glossura) annectans Dressler (Hymenoptera, Apidae, Euglossini)

Abstract: ABSTRACT. Three nests of Euglossa (Glossura) annectans Dressler, 1982 were obtained from trap nests at Serra do Japi, Jundiai, Sao Paulo State, Brazil. The bees nested in bamboo cane (one nest) and in wooden-boxes (two nests). SolitalY (two cases) and pleometrotic (one case) foundations were observed. Two nests were re-used once by two females working in each of them. Re-using females that shared the nests were of the same generation and each built, provisioned and oviposited in her own cells, characterizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
28
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 6 publications
(8 reference statements)
6
28
0
5
Order By: Relevance
“…Euglossa, with 122 described species (Nemésio, 2009), is the only genus of euglossines that presents species with multifemale nests, task allocation and overlapping generations (Garófalo, 1985;Ramírez-Arriaga et al, 1996;Garófalo, 2004, 2009;Cocom Pech et al, 2008) as well as solitary and communal species (Dressler, 1982;Young, 1985;Roberts and Dodson, 1967; Corresponding author: S.C. Augusto, scaugusto@umuarama.ufu.br * Manuscript editor: Stan Schneider Garófalo et. al., 1998;Soucy et al, 2003;Otero et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Euglossa, with 122 described species (Nemésio, 2009), is the only genus of euglossines that presents species with multifemale nests, task allocation and overlapping generations (Garófalo, 1985;Ramírez-Arriaga et al, 1996;Garófalo, 2004, 2009;Cocom Pech et al, 2008) as well as solitary and communal species (Dressler, 1982;Young, 1985;Roberts and Dodson, 1967; Corresponding author: S.C. Augusto, scaugusto@umuarama.ufu.br * Manuscript editor: Stan Schneider Garófalo et. al., 1998;Soucy et al, 2003;Otero et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies carried out in remnants of Atlantic rainforest in southeastern Brazil have revealed variation in the frequencies of males belonging to the euglossine bee species Eufriesea violacea (Blanchard) (Rebêlo and Garófalo, 1991;Garófalo et al, 1998;Jesus and Garófalo, 2000), a very seasonal species of bees mainly found in south and southeastern Brazilian Atlantic rainforest (Wittmann et al, 1989;Rebêlo and Garófalo, 1991;Peruquetti and Campos, 1997). Sofia and Suzuki (2004) have reported that a reduction in fragment size negatively affected the frequency of E. violacea males.…”
mentioning
confidence: 99%
“…Os ninhos das espécies de Euglossa podem ser aéreos, fixos em folhas, galhos, ramos de árvores ou arbustos (Dodson 1966, Dressler 1982, Young 1985, Eberhard 1988, entre material fi broso em raízes de orquídeas (Dodson 1966), em cavidades existentes, tanto em ninhos abandonados de outros insetos (Zucchi et al 1969, Garófalo 1992, como em recipientes feitos pelo homem (Garófalo 1985(Garófalo , 1992Garófalo et al 1993Garófalo et al , 1998Augusto & Garófalo 2004), ou ainda no solo (Roberts & Dodson 1967).…”
unclassified
“…O conjunto de informações agora disponível indica que E. melanotricha apresenta hábito de nidifi cação semelhante ao da maioria das espécies de Euglossa estudadas mais detalhadamente (Garófalo 1985(Garófalo , 1992Ramírez-Arriaga et al 1996;Garófalo et al 1998;Soucy et al 2003;Augusto & Garófalo 2004), ou seja, fundação solitária comprovada pelo ninho aqui descrito, e reativação do ninho por uma ou mais fêmeas, conforme relatado por Sakagami et al (1967). Por outro lado, a ausência de observações sobre o comportamento das fêmeas no interior do ninho difi culta a defi nição da estrutura social da espécie.…”
unclassified
See 1 more Smart Citation